A New Paradigm for Clostridioides difficile Infection: Atypical Presentations Correlating to Acute Gastrointestinal Dysmotility Are Associated With Increased Mortality - Emma Bishop; Steven Mileto; Tanya Ravipati; Nazim Bhimani; Eugene Athan; Ravindranath Tiruvoipati; Dena Lyras (Clinical Infectious Diseases, 2026)
Abstract Background Damage to the enteric nervous system in murine Clostridioides difficile infection (CDI) has recently been postulated as an explanation for the paradoxical dysmotility, including ileus, observed in a disease generally characterized by diarrheal onset. However, the clinical spectrum and mortality implications of acute gastrointestinal dysmotility remain under-explored in human CDI. Methods We conducted the first retrospective cohort study of hospitalized adults (≥18 years) with CDI at a single tertiary health service in Australia between January 2018 and December 2021, defining clinical and radiologic features of gastrointestinal dysmotility at diagnosis, during admission, and in relation to the timing of diarrheal onset. Atypical presentations were defined as 1 or more CDI-associated symptoms persisting for >24 hours before diarrheal onset. Outcomes included time to diagnostic testing and directed therapy, 30- and 90-day mortality. Multivariable logistic and Cox regression models were used assessing independent risk factors associated with death. Results Among 467 CDI episodes, dysmotility occurred in 32% at diagnosis and persisted radiologically for up to 6 weeks. Atypical presentations (91/467 [19.5%] episodes) were associated with significantly delayed treatment (median, IQR 4 [1–9] versus 2 [0–8] days, P < .001) and increased 90-day all-cause mortality compared with typical presentations (24.2% versus 9.6%, HR 2.62 [1.51–4.57], P = .001). Small-bowel involvement was identified in 44/270 (16.3%) baseline imaging episodes. Conclusions Both large- and small-bowel dysmotility occur frequently in hospitalized adults with CDI, contributing to diagnostic delays and increased mortality among patients with atypical presentations. These findings support extension of global CDI guidance addressing diagnostic pathways and empiric therapy.